Is It Possible for the Media and Government to Collaborate in Journalism? - Dudi Iskandar; Ratna Nuraini; Didik Hariyadi Raharjo; liliyana (UPT Publikasi Ilmiah UNISBA, 2026)
The fact is that government performance must be monitored. The media is one of the supervisors, and journalism is a form of such supervision. This phenomenon is evident in the Merdeka Barat Forum 9 (FMB9) of the Indonesian Ministry of Communications and Digital. In FMB9, the media and government public relations collaborated to form a newsroom and carry out journalism in general. This study aimed to describe, analyze, and criticize the construction of collaborative journalism between the media and government public relations that had occurred in the FMB9. This study found several points using participant observation, interviews, and library research. In the digital era, government public relations must be able to produce news similarly to mainstream media. There is a high demand for media news production and dissemination in this era. Collaboration between the media and government public relations represents a new practice of journalism. The collaboration of media with government public relations in journalism is a relatively new phenomenon in Indonesia. The implications of this study show the emergence a new type of collaborative journalism called government public relations journalism.